2013
DOI: 10.1016/j.toxicon.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing activity and protective immunity to ricin toxin conferred by B subunit (RTB)-specific Fab fragments

Abstract: SylH3 and 24B11 are murine monoclonal antibodies directed against different epitopes on ricin toxin’s binding (RTB) subunit that have been shown to passively protect mice against ricin challenge. Here we report that Fab fragments of SylH3 and 24B11 neutralize ricin in a cell based assay, and in a mouse challenge model as effectively as their respective full length parental IgGs. These data demonstrate that immunity to ricin can occur independent of Fc-mediated clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…We speculate that RTB-B7 likely recognizes a conformation-dependent epitope based on its poor binding in Western blot analysis. 4 We have recently reported that there are two types (I and II) of RTB-specific neutralizing mAbs (1,15). Type I neutralizers are postulated to prevent RTB from binding to its receptors, thereby inhibiting toxin internalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that RTB-B7 likely recognizes a conformation-dependent epitope based on its poor binding in Western blot analysis. 4 We have recently reported that there are two types (I and II) of RTB-specific neutralizing mAbs (1,15). Type I neutralizers are postulated to prevent RTB from binding to its receptors, thereby inhibiting toxin internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Recent high profile incidents involving ricin-laden envelopes addressed to members of the United States Congress and the President have accelerated efforts by the Department of Defense and the National Institutes of Health to develop countermeasures against the toxin (10,11). We and others have produced a large collection of RTA-and RTB-specific murine and chimeric mouse-human mAbs with toxin-neutralizing activity in vitro and in vivo (1,(12)(13)(14)(15)(16). Although many of these mAbs have therapeutic potential, funding agencies are increasing moving away from the "one bug, one drug" model of biodefense therapeutics to more broad-based platform technologies that can provide rapid onset against similarly acting biothreat agents.…”
mentioning
confidence: 99%
“…For example, SylH3 is a potent inhibitor of ricin-receptor interactions but only marginally effective at neutralizing ricin when pre-bound to cell surfaces, while 24B11 only partially inhibits toxin-receptor interactions but is highly effective at neutralizing ricin when toxin is pre-bound to cells [27], [28]. In an effort to better characterize RTB-B7, we first examined its ability to inhibit ricin from binding to the surrogate receptor ASF.…”
Section: Resultsmentioning
confidence: 99%
“…Surface-bound 24B11 is subsequently endocytosed as a toxin:antibody complex and interferes with retrograde transport of ricin to the TGN [27]. We have also reported that SylH3 and 24B11 Fab fragments were as effective as the full length IgGs at neutralizing ricin in vitro and in vivo , indicating that in the case of SylH3 and 24B11, neither bivalency nor Fc-domains are necessary determinants of toxin-neutralizing activity [28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, neutralization of anthrax toxin is modulated by FcR-mediated clearance though the action of specific IgG subclasses [91,92]. In the case of ricin toxin, the contribution of Fc-mediated neutralizing activity in vivo remains up for debate [84,87,93]. Indeed, very little is known about the exact mechanisms by which ricin is neutralized in vivo .…”
Section: F Key Challenges Moving Forward In Ricin Toxin Vaccine Devementioning
confidence: 99%